Enablers of sexual and reproductive health and rights interventions in low- and middle-income countries. Insights from capacity development projects implemented in 13 countries in Africa and Asia. Issue 1 (31st December 2022) - Tumwine, Gilbert; Östergren, Per-Olof; Agardh, Anette; Okong, Pius; Asamoah, Benedict Oppong
ABSTRACT: Background: The global community has committed to achieving universal access to sexual and reproductive health and rights (SRHR) services, but how to do it remains a challenge in many low-income countries. Capacity development is listed as a means of implementation for Agenda 2030. Although it has been a major element in international development cooperation, including SRHR, its effectiveness and circumstances under which it succeeds or fails have limited evidence. Objective: The study sought to examine whether improvement in team capacity of SRHR practitioners resulted in improved organisational effectiveness and/or improved SRHR outcomes in low-income countries. Methods: The study involved 99 SRHR interventions implemented in 13 countries from Africa and Asia. Self-reported evaluation data from healthcare practitioners who participated in a capacity development international training programme in SRHR was used. The training was conducted by Lund University in Sweden between 2015 and 2019. Logistic regression models were used to examine the association between improved team capacity, improved organizational effectiveness and improved SRHR outcomes, for all the 99 interventions. Adoption of new SRHR approaches (guidelines and policies), media engagement, support from partner organisations and involvement of stakeholders were assessed as possible confounders. Results: Improved team capacity, support from partner organisations and media engagement were positively associated with improved organisational effectiveness. Improved team capacity was the strongest predictor of organisational effectiveness even after controlling for other covariates at multivariate analysis. However, adopting new SRHR approaches significantly reduced organisational effectiveness. Furthermore, support from partner organisations was positively associated with increased awareness of and demand for SRHR services. Conclusions: Successful implementation of capacity development interventions requires an enabling environment. In this study, an SRHR training programme aiming at improving team capacity resulted in an improvement in organisational effectiveness. Support from partner organisations and media engagement were key enablers of organisational effectiveness.